A vacuum melting forming method for high-transparency synthetic quartz ingot for a perspective mirror
Patent Information
- Application Number
- CN202611131422.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-30
AI Technical Summary
然而,该技术仍存在以下不足:(1)步骤(4)充入氦气至一个大气压的常规压力,对羟基脱除效率的提升有限;(2)步骤(5)中二次抽真空至≤10Pa后进行高温玻璃化,虽然有利于气泡排出,但在高温玻璃化过程中没有辅助保压措施,导致玻璃中残留气泡仍无法完全消除;(3)冷却过程中未采取压力控制,石英锭在冷却收缩过程中易产生热应力,影响大口径锭体的光学均匀性和机械强度
本发明将氦气压力提升至0.5~1.2MPa。在高压氦气环境下,氦气分子在二氧化硅疏松体孔隙中的渗透深度和扩散速率显著增加,可高效带出羟基缩合反应生成的≡Si-O-Si≡键合态水分子。同时,加压降低了水蒸气分压,驱动反应平衡正向移动。实验表明,该工艺可将羟基含量降至3ppm以下,优于现有技术的5ppm水平。
Smart Images

Figure CN123003125A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-purity quartz glass manufacturing technology, specifically relating to a vacuum melting molding method for high-transmittance synthetic quartz ingots used in lenses. Background Technology
[0002] Quartz glass, due to its excellent optical transmittance, extremely low coefficient of thermal expansion, good chemical stability, and radiation resistance, has become a core material in military optical systems such as military-grade telescopes, optical guidance windows, and high-energy laser protection devices. With the rapid development of modern precision-guided weapons, optoelectronic reconnaissance equipment, and laser weapons, higher requirements are being placed on the optical uniformity, transmittance, radiation resistance, and dimensional specifications of quartz glass optical windows. Especially for transmission-type optical systems, the full-spectrum transmittance of quartz glass directly determines the system's detection sensitivity and effective range.
[0003] The mainstream production processes for synthetic quartz glass include the direct method and the indirect two-step synthesis method. The direct method, such as the electrofusion method and the gas melting method, directly melts natural quartz sand or synthetic silica raw materials at high temperatures to produce quartz glass. However, the direct method suffers from an excessively high hydroxyl (-OH) content—hydroxyl groups are introduced during the synthesis process by combustion in an oxyhydrogen flame. The presence of hydroxyl groups significantly reduces the infrared transmittance of quartz glass and degrades its thermal properties. For military optical systems requiring wide-band light transmission, the absorption peaks of hydroxyl groups near 2.7μm and 2.2μm cause fatal optical attenuation. The indirect two-step synthesis method is currently the main technical route for producing high-purity synthetic quartz glass. The process involves first hydrolyzing a chlorine-free silicon compound in a flame to generate silica particles, which are then deposited to form a silica porous body. This porous body is then vitrified at a specific temperature to obtain a quartz glass ingot.
[0004] Patent CN104271519B discloses a method for manufacturing synthetic quartz glass grains. This method involves purifying and vitrifying SiO2 particles in a rotary oven. However, this method is primarily for quartz glass grains rather than large-format ingots, and the process is complex, making it unsuitable for the production of large-diameter military optical window materials. Patent CN110183100A discloses a method for preparing quartz glass using large-format silica porous bodies. This patent achieves the preparation of large-format quartz glass with diameters ranging from Φ500 to Φ1100 mm through a two-stage vacuum process combined with inert gas filling. The resulting glass exhibits a hydroxyl content of <5 ppm and a chlorine content of <1 ppm, with high transmittance across the entire spectrum. However, the technology still has the following shortcomings: (1) In step (4), filling helium to a conventional pressure of one atmosphere has limited effect on improving the efficiency of hydroxyl removal; (2) In step (5), the secondary vacuuming to ≤10Pa followed by high-temperature vitrification is beneficial for bubble removal, but there are no auxiliary pressure holding measures during the high-temperature vitrification process, resulting in the inability to completely eliminate residual bubbles in the glass; (3) No pressure control is adopted during the cooling process, and the quartz ingot is prone to thermal stress during the cooling and shrinkage process, which affects the optical uniformity and mechanical strength of the large-diameter ingot. In addition, the patent with publication number CN120573935A discloses a processing method for high-purity quartz glass and a high-pressure vacuum electric melting furnace, which uses a high-pressure environment of up to 2MPa in combination with a directional solidification process. However, this technology is mainly aimed at the melting method rather than the vitrification process of porous bodies, and the directional solidification process still has the problem of uneven temperature field in terms of solidification interface control.
[0005] For military-grade optical lenses, current synthetic quartz ingot preparation technology still faces three major challenges: First, how to reduce the hydroxyl content to below 3ppm under large-format conditions, especially with a diameter ≥500mm, to meet the light transmission requirements of short-wave infrared and mid-wave infrared bands; Second, how to effectively eliminate microbubbles during the vitrification process, controlling the bubble level to within level 1, and avoiding the scattering and attenuation of incident light by bubbles; Third, how to eliminate the thermal stress inside the quartz ingot to ensure the dimensional stability and optical uniformity of large-aperture optical windows during processing and use. Summary of the Invention
[0006] The purpose of this invention is to provide a vacuum melting molding method for high-transmittance synthetic quartz ingots used in optics. The method aims to achieve low hydroxyl content, low bubble formation, and low stress in large-size synthetic quartz ingots through an alternating vacuum and high-pressure process, thereby meeting the requirements of military optical windows for high transmittance, large aperture, and excellent optical uniformity.
[0007] To achieve the above objectives, the technical solution of the present invention is to design a vacuum melting molding method for a high-transmittance synthetic quartz ingot used in a fluoroscopy lens, comprising the following steps: (1) Preparation of porous silica: High-purity silicon tetrachloride was used as raw material to synthesize porous silica by chemical vapor deposition. The porous silica had a diameter of Φ500~Φ1100mm, a height of 500~1000mm, and a density of 0.5~0.8g / cm³. 3 ; (2) Loading the furnace: Place the loose silica obtained in step (1) into the crucible, cover the crucible with the lid, and place it in the center of the vacuum melting furnace; (3) First vacuuming: Evacuate the vacuum furnace to ≤20Pa; (4) Low temperature preheating and dehydroxylation: The temperature inside the vacuum melting furnace is raised from room temperature to 600~1500℃ at a heating rate of 30~60℃ / h. During the heating process, the vacuum degree inside the furnace is kept ≤20Pa so that the hydroxyl groups in the silica loose body are fully removed under vacuum conditions. (5) High-pressure helium constant temperature treatment: High-purity helium is introduced into the vacuum melting furnace until the furnace pressure reaches 0.5~1.2MPa, and the temperature is kept constant at 600~1500℃ for 10~80h; (6) Secondary vacuuming: The vacuum degree inside the vacuum melting furnace is reduced to ≤10Pa; (7) High temperature vitrification: The temperature inside the vacuum melting furnace is raised from 600~1500℃ to 1550~1700℃ at a heating rate of 60~120℃ / h, and kept at a constant temperature for 2~10h, so that the silica porous body is completely vitrified under vacuum conditions. (8) High-pressure nitrogen pressure holding: While the vacuum melting furnace is continuously heated and the temperature is kept constant, high-purity nitrogen is introduced into the vacuum melting furnace until the furnace pressure reaches 1.0~2.0MPa, and the pressure is held for 20~60min; (9) Cooling and molding: Stop heating, maintain the pressure inside the furnace ≥1.0MPa, and take out the quartz ingot product after the vacuum melting furnace has cooled naturally to room temperature.
[0008] A further technical solution is that the heating rate in step (4) is 40~50℃ / h, the final temperature is 1100~1300℃, and the constant temperature time is 20~50h.
[0009] A further technical solution is that the purity of the high-purity helium gas mentioned in step (5) is ≥99.999%, and the gas is filled until the gas pressure inside the furnace reaches 0.8~1.0MPa.
[0010] A further technical solution is that the heating rate in step (7) is 80~100℃ / h, the final temperature is 1600~1650℃, and the constant temperature time is 4~6h.
[0011] A further technical solution is that the purity of the high-purity nitrogen gas mentioned in step (8) is ≥99.999%, and the gas is filled until the gas pressure inside the furnace reaches 1.2~1.8MPa, and the pressure holding time is 30~50min.
[0012] A further technical solution is that the crucible is made of high-purity graphite, and the bottom of the crucible is provided with densely distributed exhaust vents.
[0013] A further technical solution is that the hydroxyl content of the quartz ingot product is <3ppm, the chlorine content is <1ppm, the transmittance in the 200~700nm wavelength band is ≥92%, and the bubble grade reaches level 1.
[0014] The advantages and beneficial effects of this invention are as follows: This invention increases the helium pressure to 0.5~1.2 MPa. Under high-pressure helium, the penetration depth and diffusion rate of helium molecules in the pores of porous silica significantly increase, efficiently carrying out ≡Si-O-Si≡ bonded water molecules generated by the hydroxyl condensation reaction. Simultaneously, the increased pressure reduces the partial pressure of water vapor, driving the reaction equilibrium to the forward direction. Experiments show that this process can reduce the hydroxyl content to below 3 ppm, superior to the 5 ppm level of existing technologies.
[0015] This invention further optimizes the matching relationship between the heating rate and the isothermal parameters. High-temperature glassization is carried out in a high vacuum environment of ≤10Pa, which can fully remove residual gas between silica particles, mainly residual helium and trace amounts of water vapor generated by the dehydroxylation reaction; at the same time, the high temperature induces viscous flow and densification between particles, which inhibits the nucleation and growth of bubbles from the source.
[0016] This invention involves vitrification at 1550-1700℃, followed by the introduction of high-purity nitrogen to 1.0-2.0 MPa and holding the pressure for 20-60 minutes. The underlying principle is that quartz glass is in a viscoelastic state at high temperatures. Applying high-pressure nitrogen creates an external pressure significantly higher than the internal pressure of the microbubbles within the glass. According to the ideal gas law PV=nRT, the bubble volume is forcibly compressed under high pressure, and some of the gas within the microbubbles redissolves into the glass matrix under the combined effects of high pressure and high temperature. After the pressure holding period, the glass is cooled in the furnace, and the bubble volume is fixed in a compressed state, thus achieving significant optimization of the bubble grade, reaching Grade 1 standard.
[0017] This invention maintains a furnace pressure ≥1.0MPa during the cooling process, using high-pressure nitrogen as the heat transfer medium. This provides a more uniform temperature field and a more controllable cooling rate, avoiding thermal stress concentration in the quartz ingot cross-section caused by excessive temperature differences. This is especially critical for large-sized quartz ingots with diameters of Φ500~Φ1100mm—stress concentration caused by uneven cooling can lead to ingot cracking or unacceptable stress birefringence.
[0018] This invention achieves integrated preparation of large-diameter synthetic quartz ingots by constructing a complete pressure and temperature control process system encompassing vacuum dehydroxylation, high-pressure strengthening, vacuum vitrification, high-pressure defoaming, and high-pressure cooling. The resulting quartz ingots exhibit a transmittance of no less than 92% in the 200-700nm wavelength range, a hydroxyl content of less than 3ppm, a bubble grade of 1, and low stress characteristics, fully meeting the application requirements of high-end optical systems such as military-grade optical lenses. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the process flow of a vacuum melting molding method for a high-transmittance synthetic quartz ingot used in a fluoroscopy lens according to Embodiment 1 of the present invention. Figure 2 This is a schematic diagram of the vacuum melting furnace in Embodiment 3 of the present invention; Figure 3 This is a schematic diagram of the graphite crucible assembly in Embodiment 4 of the present invention; Figure 4 This is a schematic diagram of Embodiment 5 of the present invention.
[0020] In the diagram: 1. Furnace body; 2. Annular flue; 3. Furnace chamber; 4. Air duct; 5. Crucible body; 6. U-shaped exhaust pipe; 7. Chimney; 8. Four-way switching valve; 9. High-pressure nitrogen source; 10. Exhaust pipe; 11. Variable resistance throttling base plate; 12. Axial permeable guide groove; 13. Top damping sealing cover; 13a. Damping permeable layer; 13b. Sealing ring. Detailed Implementation
[0021] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0022] Example 1: As Figure 1 As shown, the present invention is a vacuum melting molding method for a high-transmittance synthetic quartz ingot used in a fluoroscopy lens, comprising the following steps: (1) Using silicon tetrachloride with a purity of ≥99.999% as raw material, axial chemical vapor deposition was used to hydrolyze SiCl4 in an oxyhydrogen flame at approximately 1000℃ to generate nano-SiO2 particles, which were then deposited on the bottom surface of a conical quartz base rod to form a structure with a diameter of Φ800mm, a height of 800mm, and a density of 0.65g / cm³. 3 A porous silica matrix; (2) Remove the silica loose body from the base rod and place it in the center of the high-purity graphite crucible. The bottom of the crucible is equipped with an exhaust vent. After covering, place it in the center of the vacuum melting furnace. (3) Evacuate the vacuum in the vacuum melting furnace to 15 Pa; (4) The furnace temperature is raised from room temperature to 1200℃ at a heating rate of 45℃ / h, and the vacuum degree is maintained at ≤20Pa during the heating process; (5) Fill the furnace with high-purity helium gas with a purity of ≥99.999% to 1.0MPa and keep it at 1200℃ for 50h; (6) Evacuate the vacuum inside the furnace to 8 Pa; (7) Increase the temperature inside the furnace from 1200℃ to 1620℃ at a heating rate of 90℃ / h and keep it at that temperature for 5h; (8) Fill the furnace with high-purity nitrogen gas with a purity of ≥99.999% to 1.5MPa and maintain the pressure for 40min; (9) High-pressure staged cooling molding: Stop heating and maintain the nitrogen pressure in the furnace at 1.5±0.05MPa by automatic gas replenishment. Perform staged cooling according to the following system: First, cool slowly from 1620℃ to 1200℃ at a rate of 30~50℃ / h, and implement temperature and pressure control throughout the process; then adjust the cooling rate to 10~20℃ / h and continue to cool down to 900℃, and maintain temperature and pressure control during this stage; when the temperature drops to 900℃, cool down to 500℃ at a rate not exceeding 50℃ / h, and switch to temperature control combined with constant pressure mode during this period; after the temperature drops below 500℃, turn off the active cooling system and switch to natural cooling to room temperature, and maintain constant pressure throughout the process.
[0023] During the 900℃→500℃ stage, heating is stopped, and the furnace body's insulation layer dissipates heat naturally. The cooling rate is monitored in real time by a temperature sensor. When the instantaneous cooling rate exceeds 50℃ / h, the PID controller drives the heating element to perform pulsed reheating, dynamically maintaining the cooling rate within the range of ≤50℃ / h. At the same time, the nitrogen pressure inside the furnace is maintained at 1.5±0.05MPa through automatic gas replenishment.
[0024] Throughout the cooling process, the nitrogen pressure inside the furnace is maintained at a constant 1.5±0.05MPa through automatic gas replenishment. After the furnace temperature drops to room temperature, the pressure is released and the quartz ingot is removed.
[0025] Testing revealed that the quartz ingot product obtained in this embodiment had the following characteristics: hydroxyl content 2.1 ppm, chlorine content 0.5 ppm, and a bubble grade of 1 (defined according to GB / T 5949-2014, defined as: per 100 cm³ of water). 3 No more than one bubble with an inner diameter ≥ 0.05 mm, and no bubbles with a diameter ≥ 0.1 mm (equivalent to the first-level internal control level of semiconductor-grade synthetic quartz). Using a 10 mm thick double-sided polished sample, the average transmittance was measured to be 93.2% in the wavelength range of 200~700 nm, and the stress birefringence was ≤ 2 nm / cm.
[0026] Example 2 differs from Example 1 in that... (1) The loose body has a diameter of Φ600mm, a height of 600mm, and a density of 0.55g / cm³. 3 ; (2)~(3) Same as Example 1; (4) The temperature is increased from room temperature to 1000℃ at a rate of 35℃ / h, with a vacuum degree ≤20Pa; (5) Fill with helium to 0.8 MPa and keep at 1000℃ for 60 hours; (6) The vacuum level is evacuated to 6 Pa; (7) The temperature was increased from 1000℃ to 1580℃ at a rate of 75℃ / h and held at that temperature for 6 hours; (8) Inflate with nitrogen to 1.2 MPa and maintain the pressure for 50 min; (9) Same as Example 1.
[0027] Test results show: hydroxyl content 2.5 ppm, chlorine content 0.6 ppm, bubble level 1, and average light transmittance 92.8%.
[0028] Comparative Example 1 Quartz ingots were prepared according to the embodiment method of the patent with publication number CN110183100A. In step (4), helium was charged to 0.1 MPa (one atmosphere), and in step (7), nitrogen was charged to 0.1 MPa. There was no high-pressure holding during the cooling stage. Test results: hydroxyl content 4.2 ppm, bubble level 2-3, average light transmittance 90.5%.
[0029] As can be seen from the comparison, this invention reduces the hydroxyl content from 4.2 ppm to 2.1 ppm by increasing the helium pressure from 0.1 MPa to 1.0 MPa through high-pressure helium dehydroxylation; increases the nitrogen pressure from 0.1 MPa to 1.5 MPa through high-pressure nitrogen defoaming, reducing the bubble level from 2-3 to 1; and significantly reduces the stress birefringence of the quartz ingot from 8-15 nm / cm in Comparative Example 2 to less than 2 nm / cm in the central region and less than 3 nm / cm in the edge region through a high-pressure staged cooling process, thus significantly improving optical uniformity and meeting the requirements of high-precision optical systems.
[0030] The method of this invention is stable and controllable, suitable for industrial mass production. The high-transmittance synthetic quartz ingots produced can be widely used in high-tech fields such as military optical guidance windows, high-energy laser protection windows, optoelectronic countermeasure optical components, and space optical systems, and have good economic and social benefits.
[0031] Comparative Example 2 (without high-pressure cooling) The operation is carried out according to steps (1) to (8) of Example 1, but step (9) is changed to: after stopping heating, the pressure inside the furnace is released to atmospheric pressure, i.e., 0.1 MPa, all air inlet valves are closed, and the furnace is allowed to cool naturally to room temperature. There are no pressure maintenance measures or graded cooling control during the cooling process. According to actual measurements, the total time for Comparative Example 2 to cool naturally from 1620℃ to room temperature is about 5 hours (of which the 1620℃→900℃ stage is about 2 hours, the 900℃→500℃ stage is about 1.5 hours, and the 500℃→room temperature stage is about 1.5 hours).
[0032] The performance comparison between Example 1 and Comparative Example 2 is shown in the table below:
[0033] The results show that although the total cooling time of Comparative Example 2 was shorter, the stress birefringence value of the resulting quartz ingot was significantly higher. The cooling process in Example 1 was controllable and the overall rhythm was stable; Comparative Example 2, due to the lack of pressure holding and graded control, had a faster cooling rate, but the stress of the resulting product was significantly higher. For military-grade optics applications, this stress level would lead to optical path distortion, failing to meet usage requirements. In Comparative Example 2, after heating was stopped and pressure was released to atmospheric pressure, the furnace was allowed to cool naturally from 1620℃ to room temperature, with a measured total cooling time of approximately 26–30 hours. Example 1 used a high-pressure graded cooling process, with a total cooling time of approximately 39–43 hours, only about 13 hours longer than Comparative Example 2, reducing stress birefringence by approximately 75%–80%. Both Example 1 and Comparative Example 2 had a bubble level of 1, indicating that bubbles were mainly eliminated during the high-temperature, high-pressure holding stage, while high-pressure graded cooling primarily suppressed thermal stress and improved optical uniformity.
[0034] Example 3: The difference from Example 1 is that, as shown in Example 3... Figure 2 As shown, the method for uniformly introducing high-pressure nitrogen is as follows: (1)~(7) are the same as in the original Example 1; (8) Valve switching and high-pressure nitrogen reverse introduction for pressure holding: While the vacuum melting furnace is continuously heated and the temperature is kept constant, high-purity nitrogen is introduced into the vacuum melting furnace to 1.5MPa and held for 40min; The vacuum melting furnace is cylindrical and vertically arranged. An annular flue 2 is provided around the furnace chamber 3 (that is, an annular flue 2 is provided inside the cylindrical side wall of the furnace body 1). Air ducts 4 are arranged in a cross shape on the furnace body between the annular flue and the furnace chamber. The annular flue and the furnace chamber are connected by the aforementioned four air ducts. A U-shaped exhaust pipe 6 is provided on the outside of the furnace body 1. A chimney 7 is installed on the U-shaped exhaust pipe. The U-shaped exhaust pipe 6 is connected to the annular flue 2. A four-way switching valve 8 is provided on the connecting pipe between the U-shaped exhaust pipe and the chimney. The four-way switching valve is connected to the U-shaped exhaust pipe, the chimney, the high-pressure nitrogen source 9, and the exhaust pipe 10 respectively. During the high-pressure nitrogen pressure holding stage, the four-way switching valve is switched from the exhaust mode to the intake pressure holding mode, and the chimney and exhaust pipeline are closed. High-pressure nitrogen is then introduced into the furnace in reverse through the four-way switching valve, U-shaped exhaust pipe, and annular flue, from the four cross-shaped air ducts. The four air ducts are evenly distributed at 90° intervals along the circumference of the furnace. High-pressure nitrogen is simultaneously and evenly injected into the furnace from four symmetrical directions, so that the nitrogen pressure distribution in the entire cross section of the furnace is uniform, achieving isostatic pressure holding treatment on the surface of the quartz ingot and effectively eliminating residual microbubbles inside the quartz ingot. (9) Valve switching and cooling molding: Stop heating and maintain the furnace pressure ≥1.0MPa; when the quartz ingot cools naturally to below 500℃, switch the four-way switching valve to the exhaust mode, open the chimney, and slowly release the furnace pressure to normal pressure. At the same time, open the air duct to assist in exhaust and accelerate cooling. After the vacuum melting furnace cools to room temperature, take out the quartz ingot product.
[0035] By reversing the original cross-shaped air duct designed for exhaust gas removal and using it as a high-pressure nitrogen inlet channel, nitrogen is simultaneously and evenly injected into the furnace from four symmetrical directions. The pressure non-uniformity of the furnace cross section is reduced from ±15% in the traditional single-pipe air inlet method to ±3%. The bubble level inside the quartz ingot is improved from level 2 to 3 in the traditional process to level 1, with a bubble diameter ≤0.1mm.
[0036] Example 4: The difference from Example 1 is that, as shown in Example 4... Figure 3 As shown, the high-purity graphite crucible in step (2) uses a graphite crucible assembly, which includes a crucible body 5, a variable resistance throttling bottom plate 11, an axial permeable guide groove 12, and a top damping sealing cover 13.
[0037] The crucible body 5 is made of high-purity isostatic graphite and is cylindrical with an inner diameter of Φ500~Φ1100mm and a wall thickness of 50~100mm. The inner wall is precision machined and subsequently ground. When three sections are randomly selected along the height direction at room temperature, the roundness is ≤0.2mm.
[0038] A variable-resistance throttling base plate 11 is detachably installed at the bottom of the crucible body 5. The variable-resistance throttling base plate 11 has several through-holes, arranged radially: in the central region with a radius of 0-40% of the crucible's inner diameter, the hole diameter is Φ2mm-Φ4mm, with an opening ratio of 5%-10%; in the edge region with a radius of 40%-100% of the crucible's inner diameter, the hole diameter is Φ6mm-Φ10mm, with an opening ratio of 15%-25%. Alternatively, a porous graphite throttling disk (not shown in the figure) with a thickness of 10-20mm is superimposed on the central region of the base plate. This throttling disk is made of porous graphite with a porosity of 20%-30%, and its venting resistance is significantly higher than that of the through-hole structure in the edge region of the base plate. Through the above-mentioned zoning of hole diameters, the gas flow resistance in the central region is significantly higher than that in the edge region, thereby inhibiting gas from concentrating and passing through the loose material from the bottom central region.
[0039] The axial permeable guide grooves 12 are 4 to 8 evenly distributed longitudinal grooves machined into the inner wall of the crucible body 5. The groove cross-section is rectangular or semi-circular, with a width of 10 to 15 mm and a depth of 5 to 8 mm. The lower end of each guide groove extends to the upper surface close to the bottom plate and maintains fluid communication with the through holes in the edge area of the bottom plate. The upper end of the guide groove terminates 10 to 30 mm from the upper end face of the crucible body, below the inner side of the top damping sealing cover 13. After the silica loose body is filled, the axial permeable guide grooves 12 form independent gas flow channels, forcing the gas passing through the throttling and variable resistance bottom plate 11 to change its flow direction and permeate from bottom to top along the side wall of the loose body, thereby realizing multi-point introduction of gas in the radial direction of the loose body and improving the uniformity of gas distribution. The guide grooves are evenly distributed circumferentially, forming multiple relatively independent gas channels, so that the gas is distributed from bottom to top along the side wall after entering the loose body and gradually permeates towards the center in the radial direction.
[0040] The top damping sealing cap 13 is fastened to the upper end of the crucible body 5. A porous high-purity graphite plate with a thickness of 5-10 mm is embedded on the inner side of the top damping sealing cap 13 as a damping and permeable layer 13a. This damping layer allows trace amounts of gas to seep out at a controlled rate, but effectively prevents the escape of loose particles. Tests show that the selected porous graphite plate generally exhibits a permeability fluctuation of no more than 20% within a process window ranging from room temperature to 1620℃ and from atmospheric pressure to 1.5 MPa, providing a relatively stable back pressure environment during the process. In addition, a wedge-shaped sealing ring 13b is provided at the joint surface between the top damping sealing cover 13 and the crucible body 5. The sealing ring is made of flexible graphite or expanded graphite, and its wedge-shaped surface faces the high-pressure side inside the furnace. The wedge angle of the sealing ring 13b is controlled between 30° and 60°. When high-pressure gas is filled into the furnace, the gas pressure acts on the wedge-shaped inclined surface, generating a component force perpendicular to the sealing surface, which causes the sealing ring to further tighten against the joint surface, forming a pressure self-tightening seal. This structure can achieve reliable sealing under conventional pressure holding and defoaming pressure, reducing the reliance on complex mechanical locking mechanisms.
[0041] The assembly and usage configuration involves placing the silica porous material on the variable resistance throttling base plate 11, covering it with the top damping sealing cap 13, and then placing the entire assembly into the furnace. During the process, due to the high flow resistance at the center of the variable resistance throttling base plate 11, when vacuuming or filling with high-pressure helium, the gas cannot directly pass through the bottom center in large quantities. Instead, it is forced to enter the axial permeable guide groove 12 through the low flow resistance zone at the edge of the base plate, and then climbs upward along the side wall of the porous material and gradually permeates radially towards the center. At the same time, the damping permeable layer 13a of the top damping sealing cap 13 has controllable permeability, which can significantly inhibit the escape of porous material particles with the airflow while maintaining constant pressure inside the furnace, so that the pressure inside the furnace can act evenly on the entire height of the porous material. This controlled three-dimensional flow field structure effectively overcomes the problems of bottom airflow short-circuiting and uneven axial dehydroxylation / exhaust caused by traditional uniformly distributed through-hole base plates, and ensures constant top defoaming pressure through pressure self-tightening sealing. In vacuum mode, the gas inside the porous body diffuses outward, is collected by the guide channel, flows downward along the guide channel, and flows into the vacuum extraction port of the furnace body through the low-resistance through-holes in the bottom plate edge area. In gas charging mode, high-pressure gas enters the low-resistance through-holes in the bottom plate edge area through the gas supply port, then enters the axial permeable guide channel and flows upward along the channel body, flowing out from the openings on the side wall and upper end of the guide channel, distributing from bottom to top along the side wall of the porous body, and gradually penetrating radially towards the center.
[0042] In existing technologies, crucible bottom plates typically have evenly distributed venting holes to minimize gas flow resistance and meet the process requirements for vacuuming and atmosphere replacement. However, in the melting of large-scale porous materials, especially those with a diameter ≥ 500 mm, this low-resistance, evenly distributed hole structure is prone to causing significant process deviations: because the flow resistance is lowest in the central bottom region, gas tends to concentrate and pass through this region during vacuuming and high-pressure filling, making it difficult to effectively penetrate the upper and middle parts of the porous material, resulting in uneven dehydroxylation and upward concentration of bubbles. Under the condition of evenly distributed holes, the central bottom region becomes the preferred channel with the least resistance due to its proximity to the upper surface of the porous material and the shortest gas penetration path, allowing a large amount of gas to escape via short-circuit, while the edges and upper and middle parts of the porous material are difficult to effectively handle. At the same time, to simplify the structure, the crucible lid is usually a flat, self-weight sealed lid, which is prone to micro-leaking at the micrometer level under high temperature and high pressure, resulting in insufficient defoaming pressure at the top.
[0043] To address the aforementioned deficiencies, this invention does not employ conventional methods of plugging leaks, such as completely sealing the bottom plate or using a hard metal seal. Instead, it takes the opposite approach, reconstructing and functionalizing the defective structure. Firstly, the bottom plate through-holes, originally designed for uniform airflow distribution, are redesigned as a non-uniform flow resistance structure with high resistance at the center and low resistance at the edges—a variable-resistance throttling bottom plate design. By artificially creating a high-resistance zone at the center of the bottom plate, the gas is forced to abandon its instinct to take shortcuts and instead seek a low-resistance path at the edges, thus naturally entering the pre-designed axial permeable guide channel. This design transforms the originally harmful short-circuiting phenomenon of bottom airflow into a driving force for guiding the gas upwards along the loose body sidewall, realizing the transformation of gas penetration from one-dimensional axial penetration to upward floating permeation along the sidewall. Secondly, addressing the problem of poor graphite sealing, complex mechanical locking mechanisms are abandoned, and instead, the high-pressure gas inside the furnace itself is used as the driving force, resulting in a wedge-shaped self-tightening graphite sealing ring. This structure reverses the risk of leakage caused by high pressure into a guarantee of enhanced high-pressure sealing. The higher the pressure, the tighter the wedge-shaped surface fits, perfectly meeting the requirements of high-temperature, high-pressure pressure holding and defoaming. Therefore, this invention, through a reverse design of using resistance instead of clogging and pressure to tighten itself, transforms a structural defect that would have led to process loss of control into a functional means of regulating flow field distribution and strengthening sealing. Without adding a complex external control system, it simultaneously solves three major problems: uniform dehydroxylation, bubble elimination, and high-temperature sealing.
[0044] Example 5: The difference from Example 4 is that, as Figure 4As shown, the inner wall surface of the axial permeable channel 12 is roughened, with the surface roughness Ra controlled within the range of 3.2~12.5μm. The inner wall surface of the axial permeable channel is also coated with a high-purity silicon carbide coating with a thickness of 50~200μm. The silicon carbide coating on the inner wall of the axial permeable channel is formed by chemical vapor deposition (CVD) or slurry coating combined with high-temperature sintering. The coating is dense and firmly bonded to the graphite matrix, effectively sealing the open structure of the graphite surface. The roughened microstructure provides physical interception and nucleation sites for suspended particles, causing high-temperature volatilized silica fine particles and impurities to preferentially adhere to the inner wall of the channel rather than the porous surface. The silicon carbide coating seals the open structure of the graphite matrix, preventing impurities in the graphite matrix from precipitating at high temperatures. The deposition and growth of silicon carbide coatings on the rough surface of a graphite substrate is not a simple leveling process, but rather a further superposition of the coating's own micro-protrusion structure while maintaining the original rough morphology. This creates a dual roughening effect of mechanical roughening and coating growth, which is beneficial for further enhancing particle trapping capabilities. The synergistic effect of these two factors makes the axial permeable channel a composite structure that combines gas flow and particle trapping functions. The roughened surface of the inner wall of the axial permeable channel and the silicon carbide coating form a particle trap, intercepting high-temperature volatile particles and impurities carried in the airflow within the channel, preventing them from depositing on the porous surface and causing contamination.
[0045] During the vacuum melting stage, the furnace operates at a high temperature of 1200-1620℃. Combined with repeated vacuuming and gas filling cycles, this creates a high-temperature gas flow containing byproduct particles. To address this particulate contamination problem, industry-standard solutions primarily follow two technical approaches: one is to improve the smoothness of the furnace wall and reduce surface roughness to decrease particle adhesion and shedding—the "smoothing" approach; the other is to perform high-precision filtration and purification of the precursor gas to reduce particulate concentration at the source—the "source interception" approach. Both solutions require significant hardware investment—the ultra-smooth inner wall processing significantly increases manufacturing difficulty and cost, while the construction and maintenance costs of ultra-high purity gas purification systems are also considerable.
[0046] This embodiment employs a completely reverse approach, contrary to the aforementioned technical path. Instead of pursuing an extremely smooth furnace wall or relying on the extreme purity of the source gas, it intentionally constructs roughened particle traps within the axial permeable guide groove 12 on the inner wall of the crucible body 5. By controlling the surface roughness Ra of the inner wall of the axial permeable guide groove within the range of 3.2~12.5μm, the rough surface provides more nucleation sites and physical interception points, causing byproduct particles carried in the gas flow to preferentially adhere to the inner wall of the guide groove as they pass through, rather than depositing on the porous surface. This design reverses the process, using contaminant particles that should be avoided as targeted objects for trapping by the guide groove, achieving precise control of particulate contamination without increasing gas purification costs or furnace wall processing costs.
[0047] Example 6: The difference from Example 1 is that a combined gas replacement method is used in steps (4) and (5). This process avoids the need for an additional independent high-purity nitrogen purging step that is usually required in the traditional quartz melting process, thereby reducing the consumption of high-purity gas and the process time. Corresponding to the overall process flow of this invention, an independent purging and replacement step is required after the second vacuuming in step (6) and before the high-purity nitrogen is introduced in step (8); however, this example can completely omit this purging step through the combined design of steps (4) and (5).
[0048] (4) High-temperature baking combined with vacuum degassing: The furnace temperature was increased from room temperature to 1200℃ at a heating rate of 45℃ / h, while maintaining a vacuum of ≤20Pa during the heating process. During this process, the moisture and trace organic pollutants adsorbed on the inner wall of the furnace and the surface of the pipes underwent thermal desorption under the synergistic effect of the high temperature of 1200℃ and continuous vacuum suction. The desorbed gaseous pollutants were discharged from the furnace through the vacuum system via the exhaust vent at the bottom of the crucible and the evacuation port of the furnace body.
[0049] In existing technologies, pipeline and furnace purging is usually carried out in a cold state, which consumes a large amount of high-purity nitrogen and incurs time costs. This invention utilizes the heating process in step (4) for in-situ baking and degassing, combining the heating stage with pipeline dehydration into a single process.
[0050] (5) High-pressure helium is introduced into the initial stage for purging and replacement: High-purity helium gas with a purity ≥99.999% is introduced into the furnace. During the initial charging phase, the furnace pressure is maintained at 0.05~0.1 MPa, and the exhaust valve connected to the furnace vent is kept slightly open to stabilize the pressure within this range. This allows the low-pressure helium gas to dynamically purge the gas supply lines and the furnace interior, carrying away residual trace amounts of air and desorption products through the exhaust vent at the bottom of the crucible. After purging for 5~10 minutes, the exhaust valve is closed, and high-purity helium gas is continued to be introduced until the pressure reaches 1.0 MPa. The furnace is then kept at a constant temperature and pressure of 1200℃ for 50 hours. In this process, the high-pressure helium gas serves as both the working gas for subsequent dehydroxylation treatment and the initial gas flow during charging, acting as a purging and replacement medium, eliminating the need for a separate nitrogen purging step.
[0051] In existing technologies, the standard operating procedure for high-purity gas systems is typically vacuuming → nitrogen purging → vacuuming → introducing process gas. This embodiment divides the nitrogen purging function in this process into two parts: step (4) high-temperature baking completes deep dehydration and degassing—the moisture adsorbed on the furnace wall is desorbed at 1200℃ and removed by a vacuum pump; step (5) high-pressure helium charging initially completes atmosphere replacement—the high-pressure helium flow physically pushes out the residual air in the pipeline and furnace. The combination of these two steps allows the independent high-purity nitrogen purging process to be completely omitted, thereby reducing the consumption of high-purity gas and process time. This design follows the idea of using the process gas itself as a purging medium, replacing the original additional nitrogen purging step with the existing high-temperature heating and helium charging stages of this process.
[0052] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A vacuum melting molding method for a high-transmittance synthetic quartz ingot used in a fluoroscopy lens, characterized in that, Includes the following steps: (1) Preparation of porous silica: High-purity silicon tetrachloride was used as raw material to synthesize porous silica by chemical vapor deposition. The porous silica had a diameter of Φ500~Φ1100mm, a height of 500~1000mm, and a density of 0.5~0.8g / cm³. 3 ; (2) Loading the furnace: Place the loose silica obtained in step (1) into the crucible, cover the crucible with the lid, and place it in the center of the vacuum melting furnace; (3) First vacuuming: Evacuate the vacuum furnace to ≤20Pa; (4) Low temperature preheating and dehydroxylation: The temperature inside the vacuum melting furnace is raised from room temperature to 600~1500℃ at a heating rate of 30~60℃ / h. During the heating process, the vacuum degree inside the furnace is kept ≤20Pa so that the hydroxyl groups in the silica loose body are fully removed under vacuum conditions. (5) High-pressure helium constant temperature treatment: High-purity helium is introduced into the vacuum melting furnace until the furnace pressure reaches 0.5~1.2MPa; (6) Secondary vacuuming: The vacuum degree inside the vacuum melting furnace is reduced to ≤10Pa; (7) High temperature vitrification: The temperature inside the vacuum melting furnace is raised from 600~1500℃ to 1550~1700℃ at a heating rate of 60~120℃ / h, and kept at a constant temperature for 2~10h, so that the silica porous body is completely vitrified under vacuum conditions. (8) High-pressure nitrogen pressure holding: While the vacuum melting furnace is continuously heated and the temperature is kept constant, high-purity nitrogen is introduced into the vacuum melting furnace until the furnace pressure reaches 1.0~2.0MPa, and the pressure is held for 20~60min; (9) Cooling and molding: Stop heating, maintain the pressure inside the furnace ≥1.0MPa, and take out the quartz ingot product after the vacuum melting furnace has cooled naturally to room temperature.
2. The vacuum melting and forming method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 1, characterized in that, The heating rate in step (4) is 40~50℃ / h, the final temperature is 1100~1300℃, and the constant temperature time is 20~50h.
3. The vacuum melting and molding method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 2, characterized in that, The purity of the high-purity helium gas in step (5) is ≥99.999%, and the gas is filled until the pressure inside the furnace reaches 0.8~1.0MPa; after reaching the set pressure, the temperature is kept constant at 600~1500℃ for 10~80h.
4. The vacuum melting and forming method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 3, characterized in that, The heating rate in step (7) is 80~100℃ / h, the final temperature is 1600~1650℃, and the holding time is 4~6h.
5. The vacuum melting and forming method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 4, characterized in that, The purity of the high-purity nitrogen gas mentioned in step (8) is ≥99.999%, and the gas is filled until the gas pressure inside the furnace reaches 1.2~1.8MPa, and the pressure holding time is 30~50min.
6. The vacuum melting and forming method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 5, characterized in that, The crucible is made of high-purity graphite, and the bottom of the crucible is provided with densely distributed exhaust vents.
7. The vacuum melting and forming method for a high-transmittance synthetic quartz ingot for a fluoroscopy lens according to claim 6, characterized in that, The quartz ingot product has a hydroxyl content of <3ppm, a chlorine content of <1ppm, a light transmittance of ≥92% in the 200~700nm wavelength band, and a bubble grade of Level 1.
Citation Information
Patent Citations
Method for manufacturing synthetic quartz glass grains
CN104271519B
Method for preparing quartz glass from large-sized silicon dioxide loose body
CN110183100A
Processing method of high-purity quartz glass and high-pressure vacuum electric melting furnace
CN120573935A